Structure and determinants of financial covenants in leveraged buyouts - evidence from an economy with strong creditor rights - Ann-Kristin Achleitner; Reiner Braun; Florian Tappeiner (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2009)
We apply control rights theory to explain the structure and determinants of financial covenants in private equity backed leveraged buyouts. We analyze 130 German transactions from 2000 to 2008, covering about 40 percent of the LBO market during this period. We consider Germany to be a superior institutional context as creditors have substantial rights in case of borrower default and contracts are negotiated more rigorously. Regarding structure we find that the financial covenant structure, in terms of number and types, is standardized and appears to be much more conservative than in the United States. Additionally, our results suggest that financial covenants are designed in a hierarchical manner, with the Debt to EBITDA covenant being the first to breach in early years. Regarding determinants we are the first, to our knowledge, to apply a direct measure of financial covenant restrictiveness, which is the real negotiated item between lead arrangers and sponsors. Our results show that financial covenant restrictiveness is significantly negatively related to the size of the private equity group, which serves as a proxy for reputation. Further we show that target-related factors, like growth and profitability, have a strong impact on financial covenant restrictiveness. With regard to transaction-based factors, increasing financial risk leads to more restrictive financial covenants.
Keywords: G21; G24; G32; G34; 330; financial covenants; leveraged buyouts; financing structure; control rights; Unternehmensfinanzierung; Eigenkapital; Kapitalstruktur; Eigentümerstruktur; Corporate Governance; Familienunternehmen; Deutschland